Sucrose promotes D53 accumulation and tillering in rice. Issue 1 (30th November 2021) - Patil, Suyash B.; Barbier, Francois F.; Zhao, Jinfeng; Zafar, Syed A.; Uzair, Muhammad; Sun, Yinglu; Fang, Jingjing; Perez‐Garcia, Maria‐Dolores; Bertheloot, Jessica; Sakr, Soulaiman; Fichtner, Franziska; Chabikwa, Tinashe G.; et al.
Summary: Shoot branching is regulated by multiple signals. Previous studies have indicated that sucrose may promote shoot branching through suppressing the inhibitory effect of the hormone strigolactone (SL). However, the molecular mechanisms underlying this effect are unknown. Here, we used molecular and genetic tools to identify the molecular targets underlying the antagonistic interaction between sucrose and SL. We showed that sucrose antagonizes the suppressive action of SL on tillering in rice and on the degradation of D53, a major target of SL signalling. Sucrose inhibits the gene expression of D3, the orthologue of the Arabidopsis F‐box MAX2 required for SL signalling. Overexpression of D3 antagonizes sucrose inhibition of D53 degradation and enables the SL inhibition of tillering under high sucrose. Sucrose prevents SL‐induced degradation of D14, the SL receptor involved in D53 degradation. In contrast to D3, D14 overexpression enhances D53 protein levels and sucrose‐induced tillering, even in the presence of SL. Our results show that sucrose inhibits SL response by affecting key components of SL signalling and, together with previous studies reporting the inhibition of SL synthesis by nitrate and phosphate, demonstrate the central role played by SLs in the regulation of plant architecture by nutrients. Abstract : See also the Commentary on this article by Finlayson, 234 : 7–9 .